Synthesis and characterization of sacha inchi (Plukenetia volubilis L.) oil-based alkyd resin - Flores, Santiago (2019)
Sacha Inchi (Plukenetia volubilis L.) is a wild oleaginous plant of the Euphorbiaceae family that grows in the Peruvian rainforest. The oil obtained from the seeds, which can reach 92% polyunsaturated fatty acid content, has been used as a raw material for the synthesis of alkyd resins. Short oil and medium oil alkyd resins in sacha inchi and linseed oil (control) were synthesized by a two-step alcoholysis-esterification process, reacting the oil with glycerol and phthalic and maleic anhydride in different proportions. The resins were structurally characterized using Fourier transform infrared (FTIR) and proton nuclear magnetic resonance (H-1 NMR) spectroscopic techniques. The physicochemical properties of the resins in the liquid state, such as the acid value, colour, viscosity and density, were evaluated. The coating performance of the cured resins was studied by measuring the touch dry and hard dry times, hardness, chemical resistance, and thermal stability and by accelerated corrosion tests. We concluded that sacha inchi oil can be used as a raw material alternative to linseed oil in the synthesis of alkyd resins for industrial applications.